Postoperative Recurrent Cholesteatoma in Rural Versus Urban Populations. Issue 4 (April 2021) - Kennedy, Kenneth L.; Connolly, Kevin M.; Albert, Christy L.; Goldman, Julie L.; Cash, Elizabeth D.; Severtson, Mark Allen
Abstract : Objective: Chronic ear disease presents a unique challenge to otolaryngologists in both rural and urban settings. Cholesteatoma remains a difficult disease to treat in rural populations due to limited healthcare access and high risk of recurrence. The purpose of this study was to determine if there are differences in surgical outcomes among patients with acquired cholesteatoma residing in rural versus urban settings. Study Design: Single-surgeon retrospective case series with chart review. Setting: Tertiary care private otolaryngology practice. Patients: One hundred twenty-two patients presenting to the Kentuckiana ENT otology and neurotology practice from January 2011 to May 2017. Main Outcome Measures: Surgical outcomes including recurrence, air-bone gap improvement, ossicular integrity, and complications were reviewed and compared between the rural and urban cohorts. Results: Presence of postoperative residual cholesteatoma (OR = 8.667, 95% CI = 2.022–37.141, p  = 0.008) and number of surgeries per patient (OR = 5.185, 95% CI = 1.086–24.763, p  = 0.024) were significantly increased among patients in rural nonmetropolitan areas. No significant differences were found when comparing risk of recurrence, size of cholesteatoma, presence of complications, air-bone gap improvement, and ossicular chain integrity. There were significantly more second-look surgeries performed in privately insured patients (OR = 8.582, 95% CI = 1.937–38.017, p  = 0.001). Conclusions: Patients in rural communities have an increased number of surgeries and postoperative risk for residual cholesteatoma compared to patients residing in urban settings. This study provides the basis for larger, multicenter, prospective examinations of outcomes among urban versus rural patients, which would enable a better understanding of difference in surgical outcomes between rural and urban cohorts. Level of Evidence: IV